Creating European Public Spheres: Legitimising EU Law Through a Reconfiguration of European Political Parties - Lennart Laude (European Papers (www.europeanpapers.eu), 2021)
(Series Information) European Papers - A Journal on Law and Integration, 2021 6(2), 1151-1172 | Article | (Table of Contents) I. Introduction. - II. The importance of the public sphere for the democratic legitimacy of law. - III. Conceptualising European public spheres. - III.1. Barriers to European public spheres. - III.2. Adaptations at the EU level. - IV. Status quo of European public spheres. - IV.1. Institutions of the EU's sphere of will formation. - IV.2. The European mass media. - IV.3. The European party system. - IV.4. The impact of the non-existent party system. - IV.5. Interim conclusion. - V. A new role for political parties in the EU. - V.1. A model for the European level: political parties as communicative actors. - V.2. Changing the role of European political parties. - VI. Conclusion. | (Abstract) The European Union's political response - or the lack thereof - to the current Covid-19 pandemic has reinforced doubts about the future viability of the Union. One of the key issues decreasing the acceptance of the EU is the (perceived) lack of democratic legitimacy of EU law. This Article attempts to assess the causes for this deficit and to develop suggestions to address it. With the objective of evaluating the institutions in the EU's spheres of will formation and the public spheres, it sets out a discourse-theoretical model of democratic legitimacy as a benchmark. To create European public spheres, inclusive transnational processes of opinion formation and law-making must be institutionalised. Under the changed conditions of modern communication, adaptions to account for a fragmentation of discourse and the importance of digital public spheres are necessary; this requires an institutional focus on internet communication at the EU level. An analysis of the status quo reveals that the factual non-existence of a European party system is a decisive factor for the legitimacy deficit of EU law. Without strong European political parties as communicative actors, a void between the EU's procedures of will formation and civil society exists, and European public spheres cannot be created successfully. This structural problem can be addressed, it is argued, by freeing European political parties from the constraints currently imposed by EU law. If they are conceptualised as transnational communicative actors with adequate funding, they can create Europe-an public spheres and help to overcome the legitimacy deficit of the EU.